2015
DOI: 10.1074/jbc.m115.642124
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Sulfotransferase Is an Oxidative Stress-responsive Gene That Gender-specifically Affects Liver Ischemia/Reperfusion Injury

Abstract: Background: EST regulates estrogen homeostasis by sulfonating and deactivating estrogens. Results: Liver ischemia and reperfusion (I/R) induced the expression of EST and comprised estrogen activity in an Nrf2-dependent manner. EST ablation gender-specifically affected I/R sensitivity. Conclusion: EST is an oxidative stress responsive gene that affects liver I/R injury. Significance: Inhibition of EST, at least in females, represents an effective approach to manage hepatic I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…Xie et al revealed a feedback mechanism between Nrf2 and estrogen in liver ischemia and reperfusion (I/R) Guo et al, 2015. I/R-induced Nrf2 activation directly upregulates estrogen sulfotransferase and in turn increases estrogen breakdown, limiting Nrf2 activity and gender-dependently affecting I/R injury (Guo et al, 2015). In addition, the crosstalk of Nrf2 signaling with the PTEN-GSK-3-b-TrCP pathway and the p62-mediated autophagy pathway has been demonstrated (Komatsu et al, 2010;Ni et al, 2014;Rojo et al, 2014;Taguchi et al, 2014).…”
Section: Crosstalk Of Nrf2 and Estrogen Signaling In Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al revealed a feedback mechanism between Nrf2 and estrogen in liver ischemia and reperfusion (I/R) Guo et al, 2015. I/R-induced Nrf2 activation directly upregulates estrogen sulfotransferase and in turn increases estrogen breakdown, limiting Nrf2 activity and gender-dependently affecting I/R injury (Guo et al, 2015). In addition, the crosstalk of Nrf2 signaling with the PTEN-GSK-3-b-TrCP pathway and the p62-mediated autophagy pathway has been demonstrated (Komatsu et al, 2010;Ni et al, 2014;Rojo et al, 2014;Taguchi et al, 2014).…”
Section: Crosstalk Of Nrf2 and Estrogen Signaling In Lipid Metabolismmentioning
confidence: 99%
“…Xie et al revealed a feedback mechanism between Nrf2 and estrogen in liver ischemia and reperfusion (I/R) Guo et al, 2015. I/R-induced Nrf2 activation directly upregulates estrogen sulfotransferase and in turn increases estrogen breakdown, limiting Nrf2 activity and gender-dependently affecting I/R injury (Guo et al, 2015).…”
Section: Crosstalk Of Nrf2 and Estrogen Signaling In Lipid Metabolismmentioning
confidence: 99%
“…The establishment of the hypoxia-reoxygenation (H/R) model in vitro was performed as previous described [21]. Briefly , the primary hepatocytes were placed into serum-free DMEM medium and seeded at a density of 4×10 5 cells/well in 6-well plates, which equilibrated with 1% O 2 , 5% CO 2 , and 94% N 2.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that the expression of EST was markedly induced by I/R in both male and female mice in a time-dependent manner. [36] Mechanistically, oxidative stress-induced activation of Nrf2 was responsible for EST induction, which was abolished in the Nrf2-/- mice. We identified two Nrf2 binding sites, the antioxidant response element (ARE), in the mouse EST gene promoter and established EST as a direct transcriptional target of Nrf2.…”
Section: Regulation Of Hepatic Drug Metabolism By Liver I/rmentioning
confidence: 99%
“…Based on these results, we proposed that inhibition of EST, at least in females, may represent an effective approach to manage hepatic I/R injury. [36]…”
Section: Regulation Of Hepatic Drug Metabolism By Liver I/rmentioning
confidence: 99%